Effect of the type of LED polymerization unit on the compressive strength of conventional and bulk-fill composite resins: an in vitro study - Castilla Cabello, Alonso Humberto (2025)
Objective: To determine the effect of the type of LED polymerization unit on the compressive strength of conventional and bulk-fill composite resins. Materials and methods: Two conventional composite resins (3M Filtek® Z350 XT and Palfique® LX5), two bulk-fill composite resins (Tetric N-Ceram® Bulk Fill and 3M Filtek® One Bulk Fill), and two LED polymerization units (3M Elipar® DeepCure-L, single-wave emission, and Bluephase® N G4, polywave emission) were used. Eight experimental groups were formed, each consisting of ten specimens (n = 80). Bulk-fill resin samples were fabricated in cylindrical molds measuring 4×5 mm by applying a single 4-mm increment of material. A celluloid strip and a microscopy coverslip were used during light curing for 20 seconds. Conventional resin samples were prepared in two increments of 2 mm each. The first increment was placed in a cylindrical mold measuring 2×5 mm, following the described procedure; the specimen was then transferred to a 4×5 mm mold where the second increment was applied, repeating the same procedure. The samples were coded and stored in distilled water in an incubator (24 h, 37 °C); subsequently, they were subjected to compressive strength testing (0.5 mm/min) using a universal testing machine. Data were analyzed using the Kruskal-Wallis statistical test. Results: No statistically significant differences in compressive strength were found among the resins light-cured with the 3M Elipar® DeepCure-L unit (p < 0.105) or with the Bluephase® N G4 unit (p < 0.109). Conclusion: The type of LED polymerization unit did not significantly affect the compressive strength of the composite resins evaluated under the experimental conditions of this study.